Business Plan And Implementation Report On Business “Rizky Bouquet” - Rizka Fillah Fauziah; Ratna Roostika (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This paper is conducted with the objective of evaluating the implementation results of the Rizky Bouquet business, which was previously designed in 2023. The business was established due to the fact that many people often celebrate special moments by giving gifts to those around them, and one of the popular gifts nowadays is flower bouquets. A flower bouquet is not just a beautiful arrangement of flowers but it also has its own meaning. Rizky Bouquet is one of businesses that focused on selling flower bouquets through both physical outlets and online sales. The target market for Rizky Bouquet's products includes all demographics, ranging from university students and working professionals to older individuals. Therefore, the methodology used involves examining the results of the business design to determine whether it has been successfully realized or if discrepancies arose during the implementation process. The results of this business implementation have been successfully realized, although some gaps have been addressed. Furthermore, based on the observation results and existing opportunities, the development of this business will focus more on utilizing social media for product promotions and following current trends to remain competitive in the industry.